Proceedings of the 1st International Conference on Information Interaction in Context - IIiX 2006
DOI: 10.1145/1164820.1164843
|View full text |Cite
|
Sign up to set email alerts
|

Image retrieval by end-users and intermediaries in a journalistic work context

Abstract: This paper describes a study on the image searching behavior of end-users (journalists) and intermediaries (archivists) in a newspaper editorial office. Image queries by end-users and requests to intermediaries were analyzed, compared and categorized according to typologies from literature. The process of image selection was modeled and selection criteria were studied based on interviews, observation and a survey. The results indicate that most image queries and requests dealt with specific entities, but that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 20 publications
(19 reference statements)
5
46
0
Order By: Relevance
“…Analysis of image requests of journalists [17] found that over half were for a named person or object, and that browsing was an essential strategy, though it was not generally well supported. Similarly, a study of a newspaper image archive [22] indicated that around 40% of requests were for a named person, with a significant number of requests for general objects or themes. In a study of queries to a commercial database by professional users [14], proper nouns accounted for only 9% of queries, whereas nouns accounted for around 50% of searches, and again browsing and exploration were seen to be under-supported.…”
Section: Image Search Usagementioning
confidence: 99%
“…Analysis of image requests of journalists [17] found that over half were for a named person or object, and that browsing was an essential strategy, though it was not generally well supported. Similarly, a study of a newspaper image archive [22] indicated that around 40% of requests were for a named person, with a significant number of requests for general objects or themes. In a study of queries to a commercial database by professional users [14], proper nouns accounted for only 9% of queries, whereas nouns accounted for around 50% of searches, and again browsing and exploration were seen to be under-supported.…”
Section: Image Search Usagementioning
confidence: 99%
“…For example, Westman and Oittinen (2006), Markkula and Sormunen (2000), Ornager (1995) specialised in image needs for newspapers. Chen (2001) researched user's needs in the context of art history by analyzing queries of twenty nine students of Art History, Jorgensen and Jorgensen (2005) analysed image searches and queries, user query modification strategies, and user browsing and downloading of results through search logs from a commercial image provider.…”
Section: Related Work 21 Image Needs and Searchmentioning
confidence: 99%
“…Jörgensen and Jörgensen (2005) analyse logs from an image search engine undertaking a quantitative analysis of the session and queries. More recently Westman and Oittinen (2006) looked at image retrieval within the field of journalism and found some interesting behaviour regarding the image searching of journalists and archivists within this specialised domain. They found that 40% of queries were for a specific person, although there were a significant number of queries for general objects and themes as well.…”
Section: Related Workmentioning
confidence: 99%